Estimating the effect of low-temperature stress on the spatial distribution patterns of protein in wheat grains. (May 2022) - Shi, Kejia; Yin, Tingwei; Zhu, Yan; Liu, Bing; Tang, Liang; Cao, Weixing; Liu, Leilei
Abstract: As the major component determining wheat flour quality, protein is unevenly distributed in different grain fractions. In this study, mature wheat grains were pearled into nine fractions from the outer to the inner layers. The effects of low-temperature intensity, frequency and occurrence time on the spatial distribution patterns of grain protein were analyzed. The highest and lowest protein contents were observed in the aleurone and innermost endosperm layers under different low-temperature conditions. The contents of protein in the whole grains and each fraction were enhanced by low-temperature, and the enhancement was more obvious under low temperature applied at the booting stage. Compared with low temperature applied only at the booting stage, multiple low temperatures decreased the increase in protein content in wheat grains, which indicated that low-temperature pretreatment at the jointing stage could partly offset the effects of low temperatures on grain protein. In addition, significant linear relationships were observed between the accumulated cold degree days (ACDD) and the protein content in the whole grains and most fractions, which indicated that ACDD could be used to quantify the effect of low temperature on grain protein. Furthermore, a comparison of the relationships between grain protein and two types of ACDD indicated stronger correlations between canopy temperature-based ACDD (ACDDc ) and the protein content in the outer and middle layers, whereas stronger correlations were observed between air temperature-based ACDD (ACDDa ) and the protein content in the inner layers, which means that we should not only use the air temperature to quantify the effect of low temperature on the protein content distribution of wheat; we also need to consider the canopy temperature that is more closely related to crop development. The results provide an effective method for evaluating the effect of low-temperature stress on grain quality and a novel view for optimizing the utilization of wheat flour under low-temperature condition. Graphical abstract: Image 1 Highlights: Protein spatial distribution is more sensitive to cold stress at the booting stage. Protein content in aleurone and endosperm layers is more sensitive to cold stress. Cold stress pretreatment can partly offset later cold stress effect on protein. ACDDa can be used to quantify cold stress effect on protein content in inner layers. ACDDc can quantify cold stress effect on protein content in outer and middle layers.